Space Weaponization Oleh India Melalui Uji Senjata Anti-Satelit Pada Tahun 2019 - Andini Veronica; Haiyyu Darman Moenir; Maryam Jamilah (Hubungan Internasional Universitas Andalas, 2025)
On 27 March 2019, India announced the successful test of its kinetic Anti-Satellite space weapon (ASAT) by shooting down a Microsat-R satellite in low earth orbit. The 2019 ASAT test marked a shift in the direction of India's civilian and antiarms space policy since the country's early use of space resources. The research objective is to analyze India's reasons for arming its peaceful space through the 2019 ASAT test using a neorealism perspective, with qualitative research methods and an analytical descriptive approach from secondary data sources. The research results show that China's rise as a challenger to US hegemony and the strong space cooperation between Beijing and Islamabad have the effect of a security dilemma for India. The two countries are India's strategic rivals in the region, so India needs to build deterrence for its vital space assets, as well as an effort to balance forces. Besides that, ASAT arrangements are not yet absolute at this time causing India to need to test the weapon, given India's experience with non-nuclear state status according to the NPT regime. Keywords: Anti-Satellite Test, Neorealism, Space Security, Space Weapon, Space Weaponization.